Thermal-economic-environmental analysis on household refrigerator using a variable displacement compressor and low-GWP refrigerants. (March 2021) - Zhu, Zhennan; Liang, Kun; Li, Zhaohua; Jiang, Hanying; Meng, Zhongwei
Highlights: Compressor stroke can be tuned so that power consumption is reduced thus CO2 emissions. Indirect emissions account for 98% of the total CO2 emissions in variable displacement refrigerator. Running cost accounts for approximately 89% of the total cost. Replacement of R134a by R152a decreases CoP by 10% but reduces CO2 emissions by 8.6%. More CO2 emissions can be reduced given that part load represents 80% of operating hours. Abstract: Variable displacement compressor technology can achieve high steady-state efficiency, non-start/off operation thus high seasonal efficiency and capacity modulation. A comprehensive thermal-economic-environmental analysis of a household refrigerator with variable displacement compressor using three refrigerants (R134a, R152a and R1234yf) was presented using CoP and normalized CoP, set-up and running cost and Life Cycle Climate Performance, respectively. The results indicate that with the application of variable displacement technology, the compressor stroke can be tuned in response to heat load so that the power consumption is reduced thus the running cost and CO2 emissions. When the compressor stroke using R134a drops from 13 mm to 10 mm, the power consumption, total cost and life cycle CO2 emissions decrease by 86.3%, 56.7% and 59.9%, respectively. Running cost accounts for 89% of the total cost while indirect emissions accounts for 98% of the total CO2 emissions. Replacement of R134a by R152a will decrease the CoP by 10% but also reduce the cost and CO2 emissions by 5% and 8.6% respectively. This is comparable to increasing the R134a system CoP by 0.9. It is indicated that by adopting variable displacement technology, more CO2 emissions could be reduced given that part load represents over 80% of operating hours for refrigerators.